1978
DOI: 10.1111/j.1471-4159.1978.tb06548.x
|View full text |Cite
|
Sign up to set email alerts
|

RAT AND MOUSE BRAIN HISTAMINE N‐METHYLTRANSFERASE: MODULATION BY METHYLATED INDOLEAMINES1

Abstract: Abstract— A purification procedure for rat and mouse brain histamine N‐methyltransferase (HMT, EC 2.1.1.8) is described which achieves the preparation of 87‐fold purified rat brain and 166‐fold purified mouse brain enzyme. The purified HMT (MW 29,000) is inhibited by a number of physiologically and pharmacologically active amines, among them several methylated indoleamines, at concentrations above 5 ± 10‐6M. At concentrations below 1 ± 10‐7M, most of the methylated indoleamines stimulate HMT, provided histamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Thus. Sellinger et al [47] found that tryptamine and tyramine at 4 X 10-7 mol/1 inhib ited the methylation of 1.25 X 10-6 mol/1 of histamine, while in our study 5 X 10~6 mol/1 of tyramine and 10-5 mol/1 of tryptamine were required for a 50% inhibition of the methylation of 4 X 10-8 mol/1 of histamine.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Thus. Sellinger et al [47] found that tryptamine and tyramine at 4 X 10-7 mol/1 inhib ited the methylation of 1.25 X 10-6 mol/1 of histamine, while in our study 5 X 10~6 mol/1 of tyramine and 10-5 mol/1 of tryptamine were required for a 50% inhibition of the methylation of 4 X 10-8 mol/1 of histamine.…”
Section: Discussionmentioning
confidence: 50%
“…Various biogenic amines were inhibitors of HMT from guinea pig, rat and mouse brain and pig liver [32,34,[41][42][43]47], These enzymes appeared to be more sus ceptible to the inhibitory action of the amines than rat HMT employed in the present study. Thus.…”
Section: Discussionmentioning
confidence: 97%
“…Thithapandha and Cohn (1978) reported an apparent molecular weight greater than 100,000 for guinea pig brain HMT, based on its elution from Sephadex G-100 and its mobility in polyacrylamide gels. In contrast, Sellinger et al (1978) determined apparent molecular weights of 29,000 for both the rat and mouse brain HMT by gel filtration through Sephadex G-100. In the current study we determined an apparent molecular weight of 29,000 & 1000 for the purified guinea pig enzyme by means of gel filtration through both Sephadex G-100 and Sephadex G-200, and by SDS polyacrylamide gel electrophoresis.…”
Section: Discussionmentioning
confidence: 96%
“…Serotonin is a potent inhibitor of HMT [145][146][147] (inhibition constant, K i = 7-32 micromolar) [148][149][150]; this autacoid inhibits HMT in vivo also [151,152]. Several additional tryptophan metabolites are equipotent inhibitors-namely, tryptamine [47,153] (K i = 1.2-10 micromolar) [148][149][150] and 5-methoxytryptamine (in vivo [146,151]; K i = 1.2-90 micromolar) [149,153] if not indole [154]. According to several histaminologists, "the demonstration that plasma histamine levels rise after administration of some drugs, that the rise is accompanied by physiological responses that are known to occur after histamine injections, and that the responses are reduced by prior adminstration of antagonists of histamine, are observations establishing a causal connection between histamine and a syndrome, thus fullfi lling the criteria that an endogenous chemical is related to an effect" [155].…”
Section: Metabolic Disequilibria Tryptophan-loading and Potential (Umentioning
confidence: 99%